2017
DOI: 10.12973/eurasia.2017.01207a
|View full text |Cite
|
Sign up to set email alerts
|

Meta Didactic-Mathematical Knowledge of Teachers: Criteria for The Reflection and Assessment on Teaching Practice

Abstract: The objective of this study is to demonstrate that the criteria of didactical suitability, proposed by the theoretical framework known as the Onto-Semiotic Approach (OSA) of mathematical knowledge and instruction, are powerful tools for organizing the reflection and assessment of instruction processes carried out by mathematics teachers. To this aim, the results of a multiple case study are presented which prove that when teachers are faced with the task of evaluating processes of instruction, they employ-eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
43

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 18 publications
0
46
0
43
Order By: Relevance
“…They confessed that they did not have suitable resources or tools. This idea was also described in studies by Sriraman (2005) and Breda et al (2017), who stated that pre-service teachers must develop the competence of assessing the problems they could use, and that this competence must be developed in teacher education. A way of teaching this competence is with tasks that involve managing the educational analysis, for example, posing problems by varying a given problem or by creating a new problem, whether a certain situation is faced or due to a specific request (Malaspina, Mallart & Font, 2015).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…They confessed that they did not have suitable resources or tools. This idea was also described in studies by Sriraman (2005) and Breda et al (2017), who stated that pre-service teachers must develop the competence of assessing the problems they could use, and that this competence must be developed in teacher education. A way of teaching this competence is with tasks that involve managing the educational analysis, for example, posing problems by varying a given problem or by creating a new problem, whether a certain situation is faced or due to a specific request (Malaspina, Mallart & Font, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…We consider that a teacher must not only be able to solve mathematical problems, but also choose, modify and pose problems for educational purposes (Tichá & Hošpesová, 2013). Teachers must develop analysis and intervention skills to evaluate the problems they use (Breda, Pino-Fan & Font, 2017). These skills involve reflecting on the mathematical practice of problem solving and problem posing, and assessing problems based on certain educational criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the different indicators of the Didactical Suitability suggested by Breda et al (2017) which were suggested in the "Meta" dimension of the DMK for reflection on the practice. The indicators set conforms the Guide for Didactical Reflection that researchers discussed with the preservice teachers after each one of them taught a class to the girls.…”
Section: Data and Analysismentioning
confidence: 99%
“…By reviewing the term of the didactic sequences as a reference, it can be stated that they are consecutive and uninterrupted events that lead to an understanding of a specific topic [6]. A fundamental aspect in the didactic sequences destined to form competences is to consider a significant problem [7], this is due to the fact that education not only forms, but also is a scenario to solve problems of the context where different components are involved [8].…”
Section: Fig 1: Teaching Sequence Ratiomentioning
confidence: 99%